Identification and characterization of the ecdysteroid UDP-glycosyltransferase gene of Epinotia aporema granulovirus - Manzán, María Alejandra (2002)
The ecdysteroid UDP-glycosyltransferase (egt) gene of Epinotia aporema granulovirus (EpapGV) was cloned sequenced and its biological activity was assessed. It encodes a protein of 446 amino acids. Direct evidence that the cloned gene encodes an active EGT protein was obtained by transient expression assays in insect cells. The upstream untranslated region of the egt gene exhibits several consensus early promoter elements. Accordingly, the gene is expressed early upon infection of Epinotia aporema larvae and the EGT activity remains high until later times post infection. Sequence analyses indicate the presence of clusters of amino acid residues conserved among all the baculoviral EGTs, although their relation with proper protein folding, ligand binding and catalytic activity remain to be assessed. Phylogenetic trees consistently cluster the granulovirus EGTs separating them clearly from the nucleopolyhedroviruses.